Critical Educational Psychology - Bailey, Lucy E. (Journal of Interdisciplinary Studies in Education, 2019)
I read Stephen Vassallo’s text, Critical Educational Psychology (2017), with interest. As a faculty member in an interdisciplinary social foundations unit who often works with educational psychology colleagues and students, I inhabit a kind of epistemological borderlands in which I regularly engage with and support projects animated by theoretical foundations that differ from or conflict with those in my own terrain. Historians Adelman and Arons’ (1999) characterize “borderlands” as having “contested boundaries between colonial domains” (p. 816), a generative metaphor that might apply to intercultural exchanges in a variety of academic spaces and fields. I wondered whether Vassallo’s text, a recipient of the American Educational Studies Association’s Critical Choice Award (2018), might offer me additional insights for crossing over from my non-positivist and critical spaces to support post-positivist and realist work.